Developing a website - The Department of Social Preventive Medicine experience - Bulgiba, Awang (Faculty of Medicine, University of Malaya, 2000)
In 1999, the Department of Social and Preventive Medicine set up its website on the Internet (http://jummc.med.um.edu.my/spm/). Setting up the website was a whole new experience for the author and many new things were learnt along the way. This paper describes how the website was constructed, the problems, and solutions to all these problems. The experience of the author in setting up the SPM website may be useful to others wishing to set up their own department websites.